Hoax: An Information Society Challenge - Priatna, Yolan (Record and Library Journal, 2018)
Background of the study: Maturity, wisdom, and accuracy of the community in the use of information in an age like now is very important to do. Especially for a variety of information that has the potential to cause conflict in the community as well as information allegedly containing lies or better known as hoaxes. Purpose: This study aims to put forward conceptual ideas about how to deal with information problems that are now experienced by the community. Method: The method used in writing articles is literature study by conducting a review of relevant literature. Findings: Literature review results found that education by families, optimization of existing institutions in the community, and also the provision of information channels / media is a good and effective way to establish a culture of literacy that is good for the community. So that the hoax news chain / hoax becomes increasingly depressed and disconnected by itself because literacy culture has formed from the smallest layer of a society. Conclusion: The emergence of hoaxes is one of the serious problems in today's digital society. Therefore, literacy or literacy culture is an important capital for humans in navigating the current sea of information